2005
DOI: 10.1021/la051334a
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Na-, K-, and Ca-Montmorillonite at High Temperatures and Pressures:  A Monte Carlo Simulation

Abstract: Monte Carlo grand canonical molecular simulations on the hydration of Na-, K-, and Ca-montmorillonite show that between 333 and 533 K and 300-1300 bar Na-montmorillonite forms stable one-layer hydrates of d(001) spacings 12.64-12.38 Angstroms, K-montmorillonite of 12.78-12.59 Angstroms, and Ca-montmorillonite of 12.48-12.32 Angstroms. A two-layer hydrate of 14.80 Angstroms occurs for Na-montmorillonite at 533 K and 1300 bar, for K-montmorillonite of 15.32 Angstroms at 533 K and 1300 bar and of 14.74 Angstroms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 56 publications
3
14
0
Order By: Relevance
“…Thus, Odriozola & Guevara-Rodríguez (2004), using Monte Carlo (MC) and molecular dynamics (MD) computer simulations, concluded that where the number of water molecules per clay sheet was~40 in the simulation box, then the one-layer hydrate of Namontmorillonite yielding a basal spacing of 12.5 Å was stable to a depth of 6 km, corresponding to a temperature and pressure of 180ºC and 90 MPa respectively. Similar results for Na-montmorillonite were also obtained by de Pablo et al (2005) who also investigated the stability of the hydrates of Kand Ca-montmorillonite using MC simulation. It was found that the one-layer hydrates of Na-, Kand Ca-montmorillonites were stable at all temperatures (up to~200ºC) and pressures (up tõ 100 MPa) encountered to a depth of~6.7 km, assuming a normal geothermal (30ºC/km) and lithostatic (15 MPa/km) gradient.…”
Section: Nature Of Water In Clays and Shalessupporting
confidence: 80%
See 2 more Smart Citations
“…Thus, Odriozola & Guevara-Rodríguez (2004), using Monte Carlo (MC) and molecular dynamics (MD) computer simulations, concluded that where the number of water molecules per clay sheet was~40 in the simulation box, then the one-layer hydrate of Namontmorillonite yielding a basal spacing of 12.5 Å was stable to a depth of 6 km, corresponding to a temperature and pressure of 180ºC and 90 MPa respectively. Similar results for Na-montmorillonite were also obtained by de Pablo et al (2005) who also investigated the stability of the hydrates of Kand Ca-montmorillonite using MC simulation. It was found that the one-layer hydrates of Na-, Kand Ca-montmorillonites were stable at all temperatures (up to~200ºC) and pressures (up tõ 100 MPa) encountered to a depth of~6.7 km, assuming a normal geothermal (30ºC/km) and lithostatic (15 MPa/km) gradient.…”
Section: Nature Of Water In Clays and Shalessupporting
confidence: 80%
“…It may be argued though that even if osmotic swelling does not occur under basin conditions, the more limited crystalline swelling of smectites may still be a major mechanism in shale instability. If, however, the computer simulations of de Pablo et al (2005) concerning the arrangement of water and Na, Ca and K cations in the interlayer space of montmorillonite under basin conditions represent reality, then the one-layer hydrate for all these cations will persist stably at the temperatures and pressures prevailing to a depth of~6.7 km. It is difficult to see therefore that exchange of interlayer Na cations in the interlayer space of smectitic clays for K or Ca cations in the drilling fluid will necessarily involve a volumetric decrease of the smectite and a reduction of swelling pressure.…”
Section: Smectitic Shalesmentioning
confidence: 99%
See 1 more Smart Citation
“…This would be surprising and contrary to observations of a significant increase in Xray basal spacing on wetting Ca-montmorillonite [33,38]. There is, however, not universal agreement on this issue as some numerical simulations would indicate [39].These simulations, however, were focused on stability of Ca-montmorillonite at high temperatures and pressures.…”
Section: Mass Change Isothermsmentioning
confidence: 76%
“…Skipper et al, 1991Skipper et al, , 1995aSkipper et al, ,b, 2006Smith, 1998;Smith et al, 2006), and the origin of clay swelling and its dependency on pressure, temperature, and chemical potential (de Pablo et al, 2004(de Pablo et al, , 2005Smith et al, 2004Smith et al, , 2006. In contrast, little has been done to produce a macroscopic thermodynamic model of fluid-rock interactions that reproduces the discontinuities of volume and amount of water expelled during dehydration of clay as a function of pressure and temperature.…”
Section: Introductionmentioning
confidence: 99%